Binding of yohimbine and imipramine to platelets in depressive illness. - Braddock, L; Cowen, P; Elliott, J; Fraser, S; Stump, K (1986)
Radioligand binding to intact platelets was carried out in antidepressant-free patients and the 1 mg dexamethasone suppression test (DST) was performed. There were no differences in binding characteristics between patients and controls for either [3H]yohimbine or [3H]imipramine. There were no differences in binding between patients classified as endogenous using the Newcastle Scale, compared with non-endogenous patients, and no difference between DST suppressors and non-suppressors. The severity of depression did not affect binding values. After 4-6 weeks antidepressant treatment [3H]yohimbine binding was significantly reduced but [3H]imipramine binding was unaffected.